IMPROVING SPEAKING ABILITY USING ARTIFICIAL INTELLIGENCE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article explores the integration of Artificial Intelligence (AI) in enhancing speaking abilities among learners. Moreover, it analyzes different AI tools and methodologies to boost the speaking ability and confidence of students, providing insights into their effectiveness, productivity and implications in the realm of language education. In the end, the findings from the analysis that AI can significantly improve learners' speaking proficiency and confidence are provided with personal opinion and conclusion.